A Simulator for Investigation of Breakdown Characteristics of SiC MOSFETs - Yuanzhao Hu; Fei Liu; Xiaoyan Liu (Applied Sciences, 2024)
Breakdown characteristics play an important role in silicon carbide (SiC) power devices; however, the wide bandgap of SiC poses a challenge for numerical simulation of breakdown characteristics. In this work, a self-developed simulator employing a novel numerical processing method to prevent convergence issues, based on semi-classical transport models and including several kinds of mobility, generation and recombination models, is used to investigate the performance and breakdown characteristics of 4H-SiC MOSFETs in high-power applications. Good agreement between our simulator and an experiment and commercial TCAD was achieved. The simulator has good stability and convergence and can be used as a powerful tool to design and optimize semiconductor devices. Further, the breakdown characteristics are evaluated with different factors, including lattice temperature, device structure and doping profiles. Our results show that the doping profile plays the most important role in the breakdown voltage, followed by the device structure, while the impact of lattice temperature is found to be minimal.